2010
DOI: 10.1097/ccm.0b013e3181dfcb3b
|View full text |Cite
|
Sign up to set email alerts
|

Dry powder aerosolization of a recombinant surfactant protein-C–based surfactant for inhalative treatment of the acutely inflamed lung*

Abstract: The described dry powder aerosolizer may be applicable to surfactant therapy of acute lung injury/acute respiratory distress syndrome. This conclusion is based on four main factors. High doses comparable to those used for intratracheal instillation in humans can be generated within a relatively short time period, the device can be connected to the inspiratory limb of the ventilator circuit, the aerosolized surfactant material is biophysically fully active, and therapeutic efficacy was proven in three different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 35 publications
0
22
0
Order By: Relevance
“…Eventually, SF-aero administration would not require infants to be intubated or disconnected from ventilatory support, would allow ventilator settings to be fine-tuned (17), and would enhance the pulmonary distribution of the SF (6). However, several factors complicate the aerosol treatment of preterm neonates with exogenous SF (low lung volumes, high respiratory rates, small airways, and high viscosity of SF, among others) (18), so it is understandably difficult to design a successful therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Eventually, SF-aero administration would not require infants to be intubated or disconnected from ventilatory support, would allow ventilator settings to be fine-tuned (17), and would enhance the pulmonary distribution of the SF (6). However, several factors complicate the aerosol treatment of preterm neonates with exogenous SF (low lung volumes, high respiratory rates, small airways, and high viscosity of SF, among others) (18), so it is understandably difficult to design a successful therapy.…”
Section: Discussionmentioning
confidence: 99%
“…This model has been studied in several mammalian species, and the response to instilled active exogenous surfactant has been consistently positive. 22,39,[128][129][130][131][132][133][134][135][136][137] However, lung lavage primarily induces surfactant deficiency resembling RDS rather than ALI/ARDS, although superimposed injury from in vivo lavage and mechanical ventilation is also present. Other animal models of direct pulmonary ALI/ARDS have also responded favorably to active exogenous surfactant.…”
Section: Animal Studies Of Surfactantmentioning
confidence: 99%
“…157,158,173 Aero-sol delivery to the alveoli in normal lungs is maximal in the particle-size range 0.5-2.0 m, and it is possible to generate a stable surfactant aerosol with that particle size range from aqueous or powdered surfactant. 135,174,175 A recent study by Ruppert et al 135 demonstrated the ability to deliver substantial amounts of a powder recombinant protein C surfactant aerosol with a new aerosol generator to improve oxygenation and compliance in lung-lavaged rabbits. However, whether surfactant aerosolization can be accomplished in a sufficiently effective and efficient manner to replace instillation requires further and more detailed direct comparisons in animals and subsequently in human trials.…”
Section: Animal Studies Of Surfactantmentioning
confidence: 99%
See 1 more Smart Citation
“…20 Irrespective of delivery method, however, neither drug had 21 Survival, lung histology, and interleukin-8 levels were all better with aerosolized and instilled KL4 surfactant relative to a control population supported by CPAP alone. Ruppert et al 22 used a powder aerosolizer with Venticute, an artificial surfactant with recombinant surfactant protein C, in both lung lavage and bleomycin rabbit injury models and showed rapid normalization of oxygenation to pre-injury levels. Additionally, aerosolized Venticute restored normal lung compliance in spontaneously breathing bleomycin-injured mice.…”
Section: Aerosolized Surfactants Anti-inflammatory Drugs and Analgementioning
confidence: 99%